Rare Expression Of Van Der Wound Syndrome: A Case Report Revisited - Bangun, Kristaninta; Widayanti, Nurina; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2016)
Background: Van der Woude syndrome (VWS) is a rare developmental malformation, characterized by pits in the lower lip. Van der Woude syndrome is an autosomal dominant craniofacial syndrome with various expression: lower lip pits, cleft lip with or without cleft palate, syngnathia, hypoodontia, and ankyloglossia. Extra-oral abnormalities findings can be found: syndactily, corpus callosum dysgenesis, megacolon, ventricular septal defect and genital abnormality. Methods: We reported a case of 5-month-old male with rare expression of VWS: bilateral cleft lip and palate, syngnathia, lower lip pits, ptosis of upper left eyelid and macropenis. Results: We perform surgery to release the fibrous band to achieve satisfactory maximum mouth opening. Next we perform cheiloplasty and lower lip pit removal. Conclusion: Proper surgical intervention in VWS patients can improve feeding and prevent further temporomandibular complications. Careful examination of patients with cleft lip and lower lip pit should be done to avoid misdiagnosis.